Assessment of Professional Values Among Nurses Working in Tertiary Care Hospitals: A Descriptive Cross-Sectional - Sakeena, Syeda Riaz; Hussain, Samina Sajid (Biological and Clinical Sciences Research Journal, 2025)
Professional values form the ethical foundation of nursing practice and are essential for ensuring quality, equitable, and patient-centered care. Despite their importance, individual and organizational factors can influence the consistent application of these values in clinical settings. Objective: This study aims to assess the prevalence, perception, and application of professional values among nurses working in tertiary care hospitals in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 120 registered nurses using a structured, validated 26-item questionnaire. The Punjab Institute of Cardiology and the Mayo Hospital recruited participants through convenience sampling. Descriptive statistics summarized demographic data and item responses. Internal consistency was evaluated using Cronbach’s alpha, and construct validity was tested through the KMO measure and Bartlett’s Test of Sphericity. Results: Most female respondents (99.2%) worked primarily in emergency or general wards. Nurses agreed with integrity, patient privacy, and professional responsibility values. The lowest scores were associated with ethically sensitive decisions such as refusal of care based on personal values. The scale demonstrated high internal reliability (Cronbach’s alpha = 0.920) and strong construct validity (KMO = 0.858, Bartlett’s p < 0.001). Education level and clinical experience were positively associated with higher value adherence. Conclusion: While nurses generally recognize professional values, practical challenges hinder their consistent application. Strengthening ethical training, institutional support, and mentorship programs is essential to reinforcing value-based practice across all clinical settings.